Perspectives from Sociology: Modeling Religious Pluralism from Inward and Outward - Lehmann, Karsten (Journal of Interreligious Studies, 2015)
The last decade has witnessed a significant increase in academic research on Interreligious Dialogue (IRD). Scholars have started to interrogate the power dynamics and meaningful systematic relations that underlie dialogical activities emerging as the result of an increased religious pluralism worldwide. Against this background, this paper focuses on what can be described as ‘sociological approaches’ to the analysis of interreligious dialogue, with a particular emphasis on the concerned discussion in Germany. The paper begins with methodological reflections on the sociological discussion of IRD. To do so, it presents short descriptions of three recent sociological analyses on interreligious dialogue in Germany. The final section presents a specific reading of those analyses in order to provide further suggestions for the analysis of interreligious dialogue as a socio-cultural phenomenon.